Mathematical models to describe the volumetric shrinkage rate of red beans during drying - Corrêa, Paulo C.; Resende, Osvaldo; Garin, Silvia A.; Jaren, Carmen; Oliveira, Gabriel H. H. de (Engenharia Agrícola, 2011)
The present study aimed to determine the volumetric shrinkage rate of bean (Phaseolus vulgaris L.) seeds during air-drying under different conditions of air, temperature and relative humidity, and to adjust several mathematical models to the empiric values observed, and select the one that best represents the phenomenon. Six mathematical models were adjusted to the experimental values to represent the phenomenon. It was determined the degree of adjustment of each model from the value of the coefficient of determination, the behavior of the distribution of the residuals, and the magnitude of the average relative and estimated errors. The rate of volumetric shrinkage that occurred in bean seeds during drying is between 25 and 37%. It basically depends on the final moisture content, regardless of the air conditions during drying. The Modified Bala & Woods' model best represented the process.

O objetivo deste trabalho foi determinar a taxa de contração volumétrica de sementes de feijão (Phaseolus vulgaris L.) durante a secagem sob diferentes condições de ar, temperatura e umidade relativa, e ajustar vários modelos matemáticos para os valores empíricos observados, selecionando o que melhor representa este fenômeno. Foram ajustados seis modelos matemáticos aos dados experimentais para representar o fenômeno. Determinou-se o grau de ajuste de cada modelo através dos valores de coeficiente de determinação, do comportamento da distribuição dos resíduos e da magnitude dos erros médios relativos e estimados. A taxa de contração volumétrica que as sementes de feijão sofreram durante a secagem é em torno de 25 a 37%, e é basicamente em função do teor de água final e praticamente independente das condições do ar de secagem. O modelo de Bala e Woods modificado foi o que melhor representou o processo.
Keywords: Phaseolus vulgaris L.; Moisture content; Volume; Air- drying; Physical property; Phaseolus vulgaris L.; Teor de água; Secagem; Propriedades físicas